Mechanical loading and control of breathing in patients with severe chronic obstructive pulmonary disease. Issue 2 (February 1995) - Duranti, R; Misuri, G; Gorini, M; Goti, P; Gigliotti, F; Scano, G
Abstract : BACKGROUND–High neural drive to the respiratory muscles and rapid and shallow breathing are frequently observed in patients with chronic obstructive pulmonary disease (COPD), and both mechanical and chemical factors are thought to play a part. However, the interrelation between these factors and the modifications in the control of breathing are not clearly defined. The effects of an acute decrease in mechanical load by the administration of a high dose of a beta 2 agonist were studied. METHODS–Nine spontaneously breathing patients with severe COPD took part in the study. Criteria for entry were FEV1 of < 40% of predicted and an improvement in FEV1 of < 200 ml after inhalation of 400 micrograms fenoterol. The following parameters were measured: lung volumes, tidal volume (VT), respiratory frequency (Rf), maximal pleural pressure during a sniff manoeuvre (PPLmax), pleural pressure swings (PPLsw), lung resistance (RL), RL/PPLmax ratio, and surface electromyographic activity (EMG) of diaphragm (EDI) and parasternal (EPS) muscles. Arterial oxygen saturation (SaO2), end tidal carbon dioxide pressure (PETCO2), and the electrocardiogram were also monitored. Each variable was measured under control conditions and 20 and 40 minutes after the inhalation of 800 micrograms fenoterol. In five patients the effects of placebo were also studied. RESULTS–Fenoterol resulted in an increase in FEV1 and decrease in FRC. SaO2 did not change, while PETCO2 fell and heart rate increased. The VT increased, and Rf decreased, PPLsw fell and PPLmax increased, thus the PPLsw/PPLmax ratio fell. Both RL and RL/PPLmax also fell, and a substantial decrease in EDI and EPS was observed. Changes in PPLsw were related to changes in FEV1 and RL. Changes in VT and Rf, and EDI/TI and EPS/TI were also related to changes in PPLsw and RL/PPLmax ratio, but not to changes in FEV1. No variation was observed with placebo. CONCLUSIONS–In patients with severe COPD a decrease in inspiratory muscle loading relative to the maximal available strength, as expressed by the RL/PPLmax and PPLsw/PPLmax ratios, appears to be the major determinant of changes in breathing pattern and inspiratory muscle activity (decrease in EMG).